Mycoplasma pneumoniae Cytoskeletal Protein HMW2 and the Architecture of the Terminal Organelle - Bose, Stephanie R. (American Society for Microbiology (ASM), 2009)
The terminal organelle of Mycoplasma pneumoniae mediates cytadherence and gliding motility and functions in cell division. The defining feature of this complex membrane-bound cell extension is an electron-dense core of two segmented rods oriented longitudinally and enlarging to form a bulb at the distal end. While the components of the core have not been comprehensively identified, previous evidence suggested that the cytoskeletal protein HMW2 forms parallel bundles oriented lengthwise to yield the major rod of the core. In the present study, we tested predictions emerging from that model by ultrastructural and immunoelectron microscopy analyses of cores from wild-type M. pneumoniae and mutants producing HMW2 derivatives. Antibodies specific for the N or C terminus of HMW2 labeled primarily peripheral to the core along its entire length. Furthermore, truncation of HMW2 did not correlate specifically with core length. However, mutant analysis correlated specific HMW2 domains with core assembly, and examination of core-enriched preparations confirmed that HMW2 was a major component of these fractions. Taken together, these findings yielded a revised model for HMW2 in terminal organelle architecture.